The Influence of Information and Communication Technology (ICT) in Supporting Front Office Operational Activities at SSU, Bali - Wulandari, Ni Luh Sri; Seniartha, I Wayan; Adi, Ida Ayu Sri Puspa (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
This study aims to determine the influence of Information and Communication Technology (ICT) in supporting front office operational activities at Six Senses Uluwatu, Bali. This study uses quantitative and qualitative descriptive methods. Data were collected through questionnaires distributed to 24 front office employees with 22 statement indicators based on the Technology Acceptance Model (TAM) concept. The results showed that the majority of respondents strongly agreed with the ease of use of ICT (perceive ease of use), then the majority of employees strongly agreed with the usefulness of ICT (perceive of usefulness), and strongly agreed with the acceptance of technology (acceptance of IT) with the highest average value of 4.29. However, there are several obstacles faced in the use of software and hardware; such as frequent system errors, limited tools and devices that make it uncomfortable. This study concludes that the existence of ICT has a very important influence in supporting front office operational activities because it affects the quality of service provided to guests. Therefore, it is necessary to carry out maintenance and renewal of ICT devices periodically to overcome the obstacles that arise.